2010
DOI: 10.1016/j.jep.2010.07.053
|View full text |Cite
|
Sign up to set email alerts
|

Pyrostegia venusta attenuate the sickness behavior induced by lipopolysaccharide in mice

Abstract: The extract of Pyrostegia venusta attenuated the depressive-like and exploratory behaviors induced by lipopolysaccharide. Thus, our results supported previous claims of the usefulness of these plants in traditional therapies and suggest that these plants may be useful in the treatment of disorders that induced sickness behavior, such as flu and cold.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0
4

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 17 publications
3
24
0
4
Order By: Relevance
“…Considering the inhibitory property of PvHE on the first phase of formalin, is traditional Brazilian medicine for the treatment of various inflammatory diseases. Our previous study demonstrated that the PvHE attenuated the sickness behavior in mice, supporting the popular use of flowers of Pyrostegia venusta as treatment for the general symptoms of flu and cold (Veloso et al, 2010). However, its pharmacological actions have not been completely investigated to date.…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations
“…Considering the inhibitory property of PvHE on the first phase of formalin, is traditional Brazilian medicine for the treatment of various inflammatory diseases. Our previous study demonstrated that the PvHE attenuated the sickness behavior in mice, supporting the popular use of flowers of Pyrostegia venusta as treatment for the general symptoms of flu and cold (Veloso et al, 2010). However, its pharmacological actions have not been completely investigated to date.…”
Section: Discussionmentioning
confidence: 86%
“…The content of total flavonoids was 543 mg quercetin equivalent/g extract. Our previous reports showed that a principal constituent was identified as the flavonoid acacetin-7-O-glycopyranoside by HPLC/ DAD analysis (Veloso et al, 2010). Figure 1 shows that the PvHE significantly inhibited (F 4,35 =6.12; p=0.0009) the carrageenaninduced mice paw edema at doses of 30-300 mg/kg at 3 h post carrageenan, with inhibitions of 56.5%, 74.78% and 89.13%, for 30, 100 and 300 mg/kg, respectively.…”
Section: Total Phenols and Flavonoids Contentsmentioning
confidence: 99%
See 2 more Smart Citations
“…Além do uso ornamental, as flores e folhas dessa espécie também são utilizadas na medicina popular, como no tratamento de gripe e resfriado (MARONI et al 2006;VELOSO et al 2010).…”
Section: Introductionunclassified